Assessment of Probiotic Properties of Lactobacillus salivarius Isolated From Chickens as Feed Additives - Wang, Jian; Ishfaq, Muhammad; Guo, Yuquan; Chen, Chunli; Li, Jichang (Frontiers in Veterinary Science, 2020)
The continued use of sub-therapeutic antibiotics as feed additives in the poultry industry improved health and growth performance. However, the resulting antibiotic resistance increasingly becomes a major threat to public health. Probiotics are promising alternatives for the antibiotics used in poultry industry. The aim of this study was to evaluate the probiotic properties of Lactobacillus salivarius as feed additive in chickens. White leghorn chickens were randomly assigned to experimental groups. Effects of Lactobacillus salivarius supplementation on growth performance, resistance to Escherichia coli O78 challenge and heat-stress, and immune response after vaccinated with attenuated infectious bursal disease virus (IBDV) vaccine were determined. The results showed that Lactobacillus salivarius supplementation improved growth performance, such as weight and longer shank length, increased relative weights of the immune organs and decreased concentrations of odor-causing compounds. In addition, Lactobacillus salivarius supplementation alleviated organ injury caused by Escherichia coli O78 challenge and heat stress. Furthermore, Lactobacillus salivarius results in enhanced immune response after IBDV vaccine immunization, enhanced specific antibody and IFN-γ production, and lymphocyte proliferation. Our results revealed a tremendous potential of Lactobacillus salivarius as antibiotics’ substitute in poultry production.